2019
DOI: 10.3390/ijerph16214184
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clay Ceramsite and Biodegradable Polymers as Carriers in Pack-bed Biofilm Reactor for Nitrate Removal

Abstract: In recent years, there is a trend of low C/N ratio in municipal domestic wastewater, which results in serious problems for nitrogen removal from wastewater. The addition of an external soluble carbon source has been the usual procedure to achieve denitrification. However, the disadvantage of this treatment process is the need of a closed, rather sophisticated and costly process control as well as the risk of overdosing. Solid-phase denitrification using biodegradable polymers as biofilm carrier and carbon sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The adsorption equilibrium was observed at 16 h, where the TP concentration decreased to 0.43 mg/L, meeting the V level of "Surface water Environmental Quality Standard" (GB 3838-2002), and the equilibrium adsorption capacity was 0.2864 mg/g. As the mostly using models for description of adsorption kinetic, pseudo first-order and pseudo second-order models (Text S1) were used to fit the experimental data (Supplementary Table S8) (Chen et al, 2019). Although the correlation coefficients of both two kinetic models were similar (>0.9), the predicted adsorption capacity with pseudo first order model is 0.2995 mg/g which is close to the experimental value (0.2864 mg/g).…”
Section: The Adsorption Behavior and Mechanism Of Tp On Ptncmentioning
confidence: 57%
See 2 more Smart Citations
“…The adsorption equilibrium was observed at 16 h, where the TP concentration decreased to 0.43 mg/L, meeting the V level of "Surface water Environmental Quality Standard" (GB 3838-2002), and the equilibrium adsorption capacity was 0.2864 mg/g. As the mostly using models for description of adsorption kinetic, pseudo first-order and pseudo second-order models (Text S1) were used to fit the experimental data (Supplementary Table S8) (Chen et al, 2019). Although the correlation coefficients of both two kinetic models were similar (>0.9), the predicted adsorption capacity with pseudo first order model is 0.2995 mg/g which is close to the experimental value (0.2864 mg/g).…”
Section: The Adsorption Behavior and Mechanism Of Tp On Ptncmentioning
confidence: 57%
“…The adsorption thermodynamics was investigated through three isotherms at different temperatures (Figure 5B), through the data fitting with Langmuir and Freundlich isotherm models (Text S2) (Chen et al, 2019). It can be found that Langmuir model fitted better with the isotherms, and indicated the mono- layer adsorption process (Supplementary Table S9).…”
Section: The Adsorption Behavior and Mechanism Of Tp On Ptncmentioning
confidence: 99%
See 1 more Smart Citation